PERBEDAAN MINAT BELAJAR PADA SISWA KELAS X JURUSAN AKUNTANSI SMK NEGERI 2 PADANG MELALUI MEDIA BERUPA PERMAINAN MONOPOLI AKUNTANSI - Ariantika Ariantika; Agus Irianto; Efni Cerya (Universitas Negeri Padang, 2018)
This study aims to determine whether through the media game of accounting monopoly produces different learning interests with conventional learning in students of class X SMK N 2 Padang. This type of research is a kind of quasi experiment (quasi experiment). The population of the study were students of class X Accounting SMK N 2 Padang year lesson 2017/2018. The sampling technique is purposive sampling method (sample of consideration). The sample is the XA4 class student as the control class and XA1 as the Experiment class. Data type consists of primary and secondary data. The data collection instrument uses a questionnaire that has already passed the validation and reliability test stages. Data analysis technique is using t test different test. The results show that,